5‐Lipoxygenase promotes epithelial–mesenchymal transition through the ERK signaling pathway in gastric cancer. Issue 2 (17th August 2020) - Lin, Hao; Weng, Junyong; Mei, Haitao; Zhuang, Mingkai; Xiao, Xinzhu; Du, Fan; Lin, Liying; Wu, Juhua; Chen, Zhixin; Huang, Yuehong; Chen, Fenglin; Wang, Xiaozhong
Abstract: Background and Aim: 5‐Lipoxygenase has been reported to enhance cell proliferation, migration, and invasion. Epithelial–mesenchymal transition is considered an important process for tumor metastasis and invasion. Methods: The 5‐lipoxygenase expression levels and the prognoses in patients with gastric cancer were evaluated by immunohistochemistry and by the log‐rank test on Kaplan–Meier curves. We established 5‐lipoxygenase‐overexpressed and 5‐lipoxygenase‐silenced gastric cancer cells and measured migration, invasion, and epithelial–mesenchymal transition makers to examine the role of 5‐lipoxygenase in gastric cancer in vitro. In vivo, 5‐lipoxygenase‐overexpressed gastric cancer cells were administered into mice by subcutaneous injection, intraperitoneal injection or splenic intravenous injection to study the proliferation or metastasis of 5‐lipoxygenase in mice. Using the extracellular signal‐regulated kinase pathway inhibitor U0126 and activator tumor growth factor‐β, we investigated the mechanism of epithelial–mesenchymal transition induced by 5‐lipoxygenase in gastric cancer cells. Results: 5‐Lipoxygenase was upregulated in gastric cancer tissues and was related to poor overall survival in gastric cancer patients. 5‐Lipoxygenase promoted gastric cancer cell proliferation, migration, and invasion and induced the process of epithelial–mesenchymal transition in gastric cancer cells. In the nude mouse model, mice with gastric cancer tumors overexpressing 5‐LOX had a faster tumor growth rate and more severe abdominal and liver metastases than the control group. Inhibition of extracellular signal‐regulated kinase signaling by U0126 or activation by tumor growth factor‐β neutralized the effect of 5‐LOX overexpression or silencing on epithelial–mesenchymal transition. Conclusion: 5‐Lipoxygenase promotes epithelial–mesenchymal transition in gastric cancer by activating the extracellular signal‐regulated kinase signaling pathway.